THE EFFECT OF BODY COMPOSITION ON PHYSICAL FITNESS IN PEOPLE WITH OBESITY - Nur Azis Rohmansyah; Syahruddin; Wulan Rahmadhani; Ashira Hiruntrakul (Sport Scientific And Practical Aspects, 2025)
The aimed of study to investigate the effect of body composition on physical fitness of adults with obesity. This study applied a cross-sectional design and it involved 80 adults aged 30-45 years consisting of 46 men (12.79±0.38) and 34 women (12.77±0.46). The BMI mean scores of male and female subjects were (24.41±5.55) kg/m2 and (21.64±4.98) kg/m2 based on fitnessgram test and validated PAR-Q questionnaire. None of the subjects had moderate, good, or very good physical fitness levels. Most of the subjects have a low physical fitness level. The increase of BMI will decrease the physical fitness level.